The effects of prehabilitation on the functional status of patients undergoing total joint arthroplasty: A Literature Review - Almira Yuni Sunaryanti; Masfuri Masfuri (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background: Total Joint Arthroplasty (TJA) has been proven as the common procedure for end-stage disease in both hip and knee OA. TJA surgery is usually elective. There is a long waiting time between the diagnosis and the surgery, creating a potential for functional decline during the preoperative period that makes a greater effect of disease severity on postoperative result. Therefore, preoperative management is important in TJA preparation in allowing an opportunity window to improve function in patients waiting for TJA surgery and improve postoperative functional recovery. Preoperative exercise programs, known as prehabilitation, have been studied to improve results, before and after surgery. The implementation of prehabilitation before TJA in the recent literature has been shown has many benefits to improve functional statusObjectives: This literature review sought to assess the effects of prehabilitation on the functional status of patients undergoing TJA.Methods: This review made use of articles obtained through online search on the database of EBSCO, Science Direct, Proquest, and Scopus, with inclusion criteria having full text, published in 2016-2021, and written in English which then matched with certain specific keywords to get the appropriate article.Results: A total of 7 selected articles have been reviewed in accordance with the search objectives and the results are presented in tabular form. The results of the article indicate that the participants in this study consisted of patients who underwent TKA or THA.Conclusions: Based on a review conducted on selected articles, it was revealed that prehabilitation provides several benefits including increasing muscle strength, increasing ROM, reducing pain, reducing hospital stay duration, and allowing faster physical and functional recovery after TJA surgery.